The Effect of Enterprise Risk Management on Firm Performance in International Contexts: A Systematic Literature Review - Yulia Saftiana; Citra Triasma (Takaza Innovatix Labs Ltd., 2024)
This Systematic Literature Review (SLR) synthesizes empirical evidence on the influence of Enterprise Risk Management (ERM) on firm performance in an international context through the PRISMA protocol on 23 Scopus indexed articles (Q1-Q4). Using the lens of Agency Theory, this study shows that ERM serves as a crucial governance mechanism to mitigate information asymmetry and align managerial incentives with shareholder interests. The findings confirm the dominant positive correlation between ERM implementation and accounting and market performance metrics. However, its effectiveness is contingency and moderated by risk committee activities, internal maturity, digital transformation (Industry 4.0), and intellectual capital. This study concludes that the evolution of ERM from just a compliance instrument to a strategic asset is able to create a competitive advantage. The practical implications emphasize the need for the integration of governance and risk-aware culture to optimize corporate value in global markets.